Septic Arthritis of Hip Caused by Salmonella typhi: A Case Report - M. Shanthi; Uma Sekar; K. S. Sridharan (Case Reports in Infectious Diseases)
Salmonella typhi usually produces enteric fever and gastroenteritis. The infection may spread through blood stream and present as local suppurative lesions which may involve any site including the bone and joints. We report a case of septic arthritis of hip in a patient with systemic lupus erthematosis. The case is presented for its rarity and to highlight the atypical manifestations of Salmonella typhi in endemic regions.